Radiation and scattering of waves Leopold B. Felsen, Nathan Marcuvitz. - Felsen, Leopold B. (IEEE Press series on electromagnetic waves, 1994)
This world-renowned classic by Professors Felsen and Marcuvitz continues to abound in timely and useful materialover 20 years after it was originally published. The book contains indispensable information that remains difficult to find anywhere else in the electromagnetics and acoustics literature, and it will be useful for many years to come. Of particular interest is Chapter 4, Asymptotic Evaluation of Integrals, which is appreciated and cited worldwide. It contains an in-depth description of asymptotic techniques and formulas useful to both engineers and physicists.